KONSEP IDEAL PEMBUATAN AKTA PERJANJIAN KERJA OUTSOURCING WAKTU TERTENTU (STUDI DI BANK JATENG) - Chrys Wahyu Indrawati; Sukarmi Sukarmi (Jurnal Akta, 2017)
Research on "The Ideal Concept of Establishing a Deed of Working Outsourcing of Certain Time (Study In Bank Jateng)" aims to know and analyze outsourcing agreement for certain time in Bank Central Java still cause uncertainty to employees and the ideal concept of employee outsourcing agreement certain time. This research approaches sociological jurisprudence and data collection through interviews, document studies and bibliography, as well as qualitative data analysis.Establishment of Deed of Working Agreement of Outsourcing of Certain Time in Central Java Bank has not applied the principle of freedom of full contract or using standard agreement. The employment agreement still creates uncertainty for employees because of employment agreements such as provisions requiring employees to submit an original diploma that leads to uncertain employee futures because employees do not have a chance to find another job better and there is no provision for contract renewal. In addition, there is still the influence of Central Java Bank in the work agreement between the providers of labor with workers whereas Central Java Bank is not a party to the agreement or the worker has no legal relationship with the Central Java bank. The effect is in terms of placement of labor and the termination of the employment agreement and the absence of a guarantee whether the workers will work continuously on the employment provider. Barriers to employees who have completed a certain time outsourcing agreement that is no term extension of the contract and Bank Central Java can not intervene directly on a certain time outsourcing agreement between PT Bhumi Elang Perkasa with labor security unit that is not renewed his contract period. The solution selects recruitment of contract employees who have completed certain time outsourcing agreements as permanent employees and extend the contract period in certain time outsourcing agreement in the provision of security unit personnel between PT Bhumi Elang Perkasa and Bank Jateng Ideally Employee Employee Outsourcing Working arrangements should consider the principles of the agreement, particularly the principle of freedom of contract. Although this is very difficult because of standard agreements that have been standard applied by the company because it is related and influenced by company regulations. Companies should provide a wider protection of labor to create a balanced working relationship. One effort that can be done is to provide an opportunity for the workforce to contribute to determine the contents of the agreement and or to approve or disapprove of certain things that may be done by both parties. One of the provisions that can be accommodated is the provision of the obligation to submit a diploma as a guarantee, the terms of the certainty of employment, and the working relationship between the provider of labor, the user labor and the labor itself.Keywords: Deed, Specific Time Working Agreement, outsourcing